Understanding the physiological role and cross-interaction network of VapBC35 toxin-antitoxin system from Mycobacterium tuberculosis - Neelam Singh; Gopinath Chattopadhyay; Niranjana Sri Sundaramoorthy; Raghavan Varadarajan; Ramandeep Singh (Communications Biology)
Abstract The VapBC toxin-antitoxin (TA) system, composed of VapC toxin and VapB antitoxin, has gained attention due to its relative abundance in members of the M. tuberculosis complex. Here, we have functionally characterised VapBC35 TA system from M. tuberculosis. We show that ectopic expression of VapC35 inhibits M. smegmatis growth in a bacteriostatic manner. Also, an increase in the VapB35 antitoxin to VapC35 toxin ratio results in a stronger binding affinity of the complex with the promoter-operator DNA. We show that VapBC35 is necessary for M. tuberculosis adaptation in oxidative stress conditions but is dispensable for M. tuberculosis growth in guinea pigs. Further, using a combination of co-expression studies and biophysical methods, we report that VapC35 also interacts with non-cognate antitoxin VapB3. Taken together, the present study advances our understanding of cross-interaction networks among VapBC TA systems from M. tuberculosis.